Inheritance Relationship Between Children Born Out of Wedlock and Their Biological Fathers - Putri, Sonita Rifa Rahayu; Efendi, Faisal; Razak, Dudung Abdul; Syaputra, M. Zikri; Candra, Afrikal (Samara: Journal of Islamic Law and Family Studies, 2024)
The aim of this research is to analyze the Constitutional Court Decision Number 46/PUU VIII/2010 concerning Review of Law Number 1 of 1974 on inheritance rights between illegitimate children and their biological father. The research method used is qualitative research with a descriptive approach and a normative juridical perspective. The research results show that factors that allow someone to receive an inheritance include marital relations, kinship relations, and the emancipation of slaves. Legal considerations in Constitutional Court Decision Number 46 concerning Review of Law Number 1 of 1974 state that illegitimate children have a civil relationship with their mother and family, as well as with a man who is known to be their father based on science. Proof or other valid evidence that establishes the existence of blood relations, including civil relations with the father's family. Meanwhile, analysis of the Constitutional Court Decision Number 46 concerning Review of Law Number 1 of 1974 which is strengthened by Article 43 paragraph 1 of the Marriage Law confirms that a child's relationship with a man as his father is not solely based on the existence of a marriage bond. but it can also be based on evidence of a blood relationship between the child and the man identified as the father.